Preferensi Mahasiswa Penyiaran terhadap Model Kerja Tim Kecil Versus Tim Lengkap dalam Produksi Audiovisual - Latief, Rusman (P3M Politeknik Negeri Media Kreatif, 2026)
The development of digital technology has driven significant changes in audiovisual production practices, including in the context of teaching and learning within the Broadcasting Program. One essential competency that students must develop is the ability to work effectively in production teams, both small and full teams. This study aims to analyze the preferences of Broadcasting students at the Jakarta State Polytechnic for Creative Media regarding these two teamwork models, as well as to examine communication dynamics, effectiveness, comfort, productivity, and production quality. This study employed a qualitative approach with a descriptive technique. The research participants consisted of 12 fifth-semester students selected through purposive sampling who had experience working in both small and full teams. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed thematically. The findings indicate that students’ preferences for small and full teams were relatively balanced. Small teams were perceived as more efficient, flexible, and productive due to more direct communication and faster decision-making processes. In contrast, full teams were perceived as producing higher-quality outcomes through clear task distribution and role specialization. These findings confirm that teamwork effectiveness is strongly influenced by group and interpersonal communication patterns; therefore, the application of teamwork models in audiovisual production education should be adaptive and contextual.